This disease is "not for hospital": myths and misconceptions about cancers in Northern Nigeria - Ahmed M Sarki; Babangida L Roni (Inishmore Laser Scientific Publishing Ltd, 2019)
Cancers are one of the major chronic diseases in Nigeria, with over 100,000 new cases and 70,000 cancer deaths recorded annually. Notwithstanding the public health significance of cancers in Nigeria, there is a dearth of evidence relating to cancers in the country, with most of the few available studies conducted in the Southern regions. This paper aimed to highlight some longstanding myths and misconceptions about cancers in the Northern Nigerian region. We consulted key stakeholders including individuals, local leaders, traditional medicine practitioners, and healthcare professionals. The most common myths and misconceptions about cancers in Northern Nigeria include the following: people get cancers from mystical sources originating in the forests or bush; western medication or hospital treatment worsens cancers; and, witchcraft can be used to transmit cancers to people. Understanding the traditional beliefs and local perceptions of non-communicable diseases is invaluable for informing sustainable and effective interventions. Thus, our paper will be useful for epidemiological, anthropological, and social research into effective preventive measures for cancers in Northern Nigeria and other regions with similar entrenched traditional beliefs about cancers.